THE ROLE OF FEMALE WORKERS IN OIL PALM PLANTATIONS (A CASE STUDY IN UJONG KRUENG VILLAGE, TRIPA MAKMUR SUB-DISTRICT, NAGAN RAYA REGENCY): PERAN BURUH PEREMPUAN PERKEBUNAN KELAPA SAWIT (STUDI KASUS DI DESA UJONG KRUENG KECAMATAN TRIPA MAKMUR KABUPATEN NAGAN RAYA) - Eliza, Putri; Aslam Nur; Idria, Reza (Indonesian Journal of Islamic History and Culture, 2023)
Oil palm is one of the plantation commodities that needs to increase its production as it is a major producer of vegetable oil. The expansion of oil palm plantations has been taking place in various regions, including Aceh, particularly in Ujong Krueng Village, Tripa Makmur sub-district, Nagan Raya regency. The purpose of this research is to explore the history of female labor in oil palm plantations and understand the lives of female workers in Ujong Krueng Village. The research methods employed include observation and interviews. The results indicate that female laborers are workers in oil palm plantations who earn wages from the landowners. The emergence of women as laborers in Ujong Krueng's oil palm plantations is due to the increasing number of plantations and their rapid growth, requiring a large labor force. This provides opportunities for women who want to contribute to their family's economy. The lives of female laborers in Ujong Krueng include: firstly, women have a dual role, working both in their homes and in public spacec; secondly, some women, especially those who are widowed or whose husband is are dealing with severe illness, take on the responsibility of being breadwinners; thirdly, the economic of the community is positively impacted by income generated from oil palm plantations, meeting the basic living needs; fourthly, women are now undertaking tasks that were traditionally performed by men, such as transporting harvested produce.